2017
DOI: 10.1007/s13205-017-0989-x
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic bacteria associated with puffer fish Gastrophysus spadiceus and evaluation of their antimicrobial activities

Abstract: The present study reports the diversity of culturable bacteria associated with the puffer fish . During the study, a total of 31 strains affiliated to the genera, , and were isolated from liver, intestines, and flesh of. These strains exhibited a diverse range of metabolites as indicated by the HPLC and TLC profiles of the chemical extracts of their fermentation products. Some of these crude extracts showed strong antimicrobial activities against pathogenic bacterial strains. In addition, few crude extracts ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
1
1
Order By: Relevance
“…The obtained results of seasonal prevalence of V. alginolyticus were higher than what reported by Di et al (2017) who isolated V. alginolyticus at a prevalence of 8.57% in summer, 5.30% in autumn, 2.04% in spring and 0.81% in winter. This was in a disagreement with (Wang et al, 2017) who reported that V. alginolyticus were not associated with a particular season.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The obtained results of seasonal prevalence of V. alginolyticus were higher than what reported by Di et al (2017) who isolated V. alginolyticus at a prevalence of 8.57% in summer, 5.30% in autumn, 2.04% in spring and 0.81% in winter. This was in a disagreement with (Wang et al, 2017) who reported that V. alginolyticus were not associated with a particular season.…”
Section: Discussioncontrasting
confidence: 56%
“…increase in low temperature. Wang et al (2017) reported that Pseudomonas were isolated mainly in cold months. while these results disagreed with (Miguéis et al, 2016) who reported a lower prevalence of Pseudomonas in winter than in summer.…”
Section: Discussionmentioning
confidence: 99%